À la recherche du produit « véritable ». Les appellations d’origine en France aux xviie et xviiie siècles - Philippe Meyzie (Les Cahiers de Framespa)
Without a legal definition, the recognition of food by its geographical origin is based on reputations built by economic actors to distinguish the “genuine” product. Based on ongoing research on the reputation and market of designation of origin products, this contribution highlights the existence of designations of origin in France in the 17th and 18th centuries for increasingly varied foodstuffs and the growing mobilization of these geographical designations in different fields. The aim will be to assess the resonance of these reputations and the development of origin as a sign of quality. These brands offer a form of flexibility adapted to the functioning of the pre-industrial economy in which diversity of production and imitations served to ensure the fluidity of the market.